IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KELUARGA DI MASA PANDEMI - Agustina, Dwi (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The Covid-19 pandemic led to various changes and gave rise to culture shock in all areas of human life, especially in the field of education. Implementation of character education that was previously done in school, became a change in the application of learning from home. Considering the importance of character education for the sustainability of a dignified and superior generation. In times of pandemics, character education should not be ignored, especially for students in elementary school. The purpose of this study is to explain how the implementation of character education is applied by families in pandemic times. This research method uses qualitative research. Data is sourced from interviews, and questionnaires. Data analysis using with Miles Haberman model analysis that reduces data, presents data and draws conclusions. The results showed that parents implement character values including religious character, collaboration, nationalism, independence, and integrity 1) Religious aspects are done by example to children to worship, which is 63.8 percent of parents often do; 2) Collaboration aspect is done by involving children in activities at home, which is as much as 70.7 percent of parents do it; 3) Aspects of nationalism are done by teaching the love of the homeland through the use of uniforms and singing the national anthem on Mondays, namely 79.3 parents do; 4) Aspects of independence are done by accustoming children not to depend on others, which is 75.9 percent; and 5) Aspects of integrity are taught so that children have an honest attitude, which is as much as 56.9 percent teach children to have an honest attitude. Planting character values while at home shows good results, but needs to be improved with cooperation between family and school so that character planting can run effectively and efficiently.